Gender Assessment in Urban Transportation Case Study: Semarang City, Indonesia - Ratna Budiarti; Moh. Nurhadi (The Indonesian Journal of Planning and Development, 2017)
What and why transportation, climate change, and gender are connected?  What is the implication of transportation policy, program and plan (PPP) to gender equality and vice versa? This article aimed to construct it in the context of urban transportation in Semarang City where transportation contributes more than 50% of GHG emissions. This research investigated the relation of transportation, climate change, and gender by interviewing and exploring transportation users through a multistage random sampling. The respondents are divided into urban zones namely inner, suburb, and outskirt with a balanced number of men and women respondents in order to give equal information. The results showed three interesting findings. First, women and men have different travel patterns. Women’s preference for travelling implies more efficient energy consumption. Second, women have a higher dependency on public transport than men due to their limited transportation access (ownership and use). At the household level, men have a dominant role in determining transportation mode, type, and ownership of private vehicles. It influences the choice of transportation mode and the way women ride vehicle. Third, the differences of travel pattern and transportation between men and women implied to GHG emissions contribution. Participation of women in the design of transportation policy, program, and the plan will give a better impact on the transportation system and climate change as well as for women access to transportation.